Renewable Energy Certificate Trading through Power Exchanges in India - G P, Girish; P, Sashikala; Supra, Bharath; Acharya, Anitha (International Journal of Energy Economics and Policy, 2015)
Renewable Energy Certificate (REC) trading through power exchanges commenced in March 2011 in India. The enactment of Indian Electricity Act 2003 along with mandatory obligation of purchasing renewable power for distribution companies imposed by Central Electricity Regulatory Commission (CERC) and State Electricity Regulatory Commissions (SERC’s) has propelled REC trading in Indian Electricity market. In this study we review REC trading in India, role played by power exchanges in facilitating REC trading, policy framework promoting Renewable energy, Renewable Purchase Obligation imposed and suggests the possible policy considerations for the regulators in future. Keywords: Renewable Energy Certificate (REC), Trading, Power Exchanges, India, Renewable Purchase Obligation, Solar REC, Non-Solar REC JEL Classifications: C01; C22; C53